William Penn: Quaker Humanist - Frost, J. William 1940- (2012)
There is a tradition of Christian humanism from Erasmus, Grotius, Mornay, and Amyraut that Penn probably learnt at Saumur and that served as an undercurrent to the rest of his life. While it is impossible definitively to prove direct influence, the similarities between Amyraut’s ideas and Penn’s later perspectives make the possibility of influence likely.
Keywords: Amyraut; Grotius; Mornay; Saumur; William Penn; Humanism